Evaluation of Impact, Tensile, and Flexural Strength of Natural Wool Fiber Reinforced Polymethyl Methacrylate Denture Base Material: An In Vitro Study - Zahraa Abdulwahab Abdulrazzaq; Bayan S. Khalaf (Dental Hypotheses)
Introduction: This study was carried out to assess the effect of natural wool fiber addition on the impact, tensile, and flexural strengths of the heat-cured acrylic denture base material. Methods: Short wool fibers with and without chemical surface treatment were added to polymethyl methacrylate (PMMA) at a percentage of 0.25% by weight. A total of 90 acrylic specimens were prepared and divided into three groups according to the tests performed. Impact strength, tensile strength, and flexural strength tests were evaluated. The statistical analysis of the results data was performed using the one-way analysis of variance (ANOVA) test and Tukey’s post hoc test. Results: Impact strength improved significantly after adding silane-treated natural wool fibers to PMMA. However, the tested groups did not have significant differences in tensile and flexural strengths. Conclusion: Natural wool fibers in a percentage of 0.25% by weight could improve the impact strength of the acrylic denture base material after treatment with the silane coupling agent. At the same time, they did not significantly affect the tensile and flexural strengths with or without surface treatment.